2004
DOI: 10.1261/rna.7400704
|View full text |Cite
|
Sign up to set email alerts
|

The Euplotes telomerase subunit p43 stimulates enzymatic activity and processivity in vitro

Abstract: Telomerase is a reverse transcriptase that synthesizes telomeric DNA repeats at the ends of eukaryotic chromosomes. Although it is minimally composed of a conserved catalytic protein subunit (TERT) and an RNA component, additional accessory factors present in the holoenzyme play crucial roles in the biogenesis and function of the enzyme complex. Telomerase from the ciliate Tetrahymena can be reconstituted in active form in vitro. Using this system, we show that p43, a telomerase-specific La-motif protein from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…The phylogenetic analysis of the LAM-RRM (RRM-L) region gives a sharper distinction between these two related sets of proteins and strongly supports this previous classification. We also found that the functionally characterized ciliate p43 (EaLARP7) and p65 (TthLARP7) proteins (Aigner et al 2000(Aigner et al , 2003Aigner and Cech 2004;Witkin and Collins 2004;Stone et al 2007;Teixeira and Gilson 2007) are group 2 factors and cluster with the other protist proteins of this group. As for genuine La proteins, not all group 2 factors possess an RRM2 motif (see PsLARP7 and p65 [TthLARP7]), rendering both structural and evolutionary analyses necessary for classification.…”
Section: Phylogenetic Relationships Among the La-rrm Domains: Co-evolmentioning
confidence: 62%
See 1 more Smart Citation
“…The phylogenetic analysis of the LAM-RRM (RRM-L) region gives a sharper distinction between these two related sets of proteins and strongly supports this previous classification. We also found that the functionally characterized ciliate p43 (EaLARP7) and p65 (TthLARP7) proteins (Aigner et al 2000(Aigner et al , 2003Aigner and Cech 2004;Witkin and Collins 2004;Stone et al 2007;Teixeira and Gilson 2007) are group 2 factors and cluster with the other protist proteins of this group. As for genuine La proteins, not all group 2 factors possess an RRM2 motif (see PsLARP7 and p65 [TthLARP7]), rendering both structural and evolutionary analyses necessary for classification.…”
Section: Phylogenetic Relationships Among the La-rrm Domains: Co-evolmentioning
confidence: 62%
“…They are key member proteins of the telomerase RNP and are required for the assembly, nuclear retention, activity, and processivity of the complex (Mollenbeck et al 2003;Aigner and Cech 2004;Witkin and Collins 2004). P65 is one of the first factors binding to telomerase RNA.…”
Section: Introductionmentioning
confidence: 99%
“…These results reveal that the p65-TER complex recruits TERT in strong preference to TERT association with TER alone. After these experiments were completed, a ten-fold excess of T. thermophila TER was shown to reduce the association of E. aediculatus p43 with T. thermophila TERT 24 . Tetrahymena thermophila p65 and E. aediculatus p43 have limited sequence conservation beyond their shared homology with La proteins, differing even in the predicted consensus residues of the p65 RRM 9 ; their cognate TER stem IV regions share no primary sequence conservation and have major differences in stem lengths, bulges and potential branches 25 .…”
Section: Assembly Of a P65-ter-tert Complexmentioning
confidence: 99%
“…Structural and biochemical studies (Alfano et al 2003(Alfano et al , 2004Dong et al 2004) on the genuine La protein (LARP3) revealed specific binding of the La module to 3 ′ oligo-uridylic acid stretches (Stefano 1984;Wolin and Cedervall 2002;Teplova et al 2006;KotikKogan et al 2008). Accordingly, members of the LARP3 and LARP7 families associate predominantly with RNA polymerase III (RNAPIII) transcripts in vivo and influence their stability and/or maturation pathways (Sobel and Wolin 1999;Intine et al 2000;Aigner et al 2003;Chakshusmathi et al 2003;Aigner and Cech 2004;Prathapam et al 2005;Stone et al 2007;Copela et al 2008;Krueger et al 2008;Markert et al 2008). While other LARP family members also contain La modules, recent evidence suggested that LARP1, LARP4, and LARP6 are associated with mRNAs rather than RNAPIII transcripts (Nykamp et al 2008;Blagden et al 2009;Wang et al 2009;Weng et al 2009;Burrows et al 2010;Cai et al 2010a;Schäffler et al 2010;Zanin et al 2010;Yang et al 2011;Aoki et al 2013;Mura et al 2014;Tcherkezian et al 2014).…”
Section: Introductionmentioning
confidence: 99%